Contribution of Wave Setup to Projected Coastal Sea Level Changes. Issue 8 (3rd August 2020) - Melet, A.; Almar, R.; Hemer, M.; Le Cozannet, G.; Meyssignac, B.; Ruggiero, P.
Abstract: Along open coasts, wind waves are a key driver of coastal changes and can be major contributors to coastal hazards. Wind wave characteristics are projected to change in response to climate change, notably due to changes in atmospheric circulation patterns and the associated surface winds. Here, a first‐order estimate of projected 20‐yr mean wave setup changes, excluding extreme events and subannual variability, is provided for sandy beaches along most of the world's coastline over the middle and end of the 21st century. Calculations are based on an ensemble of wave model projections under the representative concentration pathways (RCP) 8.5 and on empirical formulations for wave setup. Projected wave setup changes are compared to other contributors currently accounted for in regional sea level projections to extend existing projections of 21st century coastal sea level changes. Projected wave setup changes exhibit a clear spatial heterogeneity and mostly average out at global scale. However, at regional or local scale, wave setup changes are a small yet nonnegligible contributor to total coastal sea level 20‐yr mean changes (which include global mean sea level rise, GMSLR) over the middle and end of the 21st century. Wave setup can be a substantial contributor to local departures of coastal sea level changes from GMSLR. Wave setup changes should therefore be included in projections of regional patterns of coastal sea level changes. The reported long‐term changes in wave setup also advocate for the inclusion of nonstationary wave contributions to projected regional patterns of coastal sea level changes, including for studies on extreme events. Key Points: Projected 20‐yr mean wave setup changes are small but can attenuate or amplify total coastal sea level changes for the 21st century Wave setup can locally be a substantial contributor to departures of coastal sea level changes from global mean sea level rise Projected 20‐yr mean wave runup changes can be large contributors to local departures from global mean sea level rise